The Teacher Strategy of Aqidah Akhlak in Fostering Akhlak Al-Karimah Students as State Islamic Senior High School 1 Indragiri Hilir - Yateno, Yateno; Hidayat, Hidayat; Ridwan, Ahmad (International Journal of Advanced Multidisciplinary, 2023)
This study examines the strategies applied by Aqidah Akhlak Teachers in developing the noble character of students at Madrasah Aliyah Negeri 1 Indragiri Hilir, with the following problem formulation: 1. What are the noble character of SMA Negeri 1 Indragiri Hilir students 2. What are the strategies applied by the teacher in fostering noble character students at SMA Negeri 1 Indragiri Hilir 3? What is the form of fostering noble character in Indragiri Hilir State Islamic High School 1? The method used by the author in collecting data includes observation, interviews, and documentation. By using this method, it is hoped that concrete data will be obtained that is by the needs of the authors in research at Madrasah Aliyah Negeri 1 Indragiri Hilir. The collected data were then analyzed through descriptive methods for qualitative data. From the results of the study, it can be concluded: first, exemplary, lectures, discussion advice, and punishment; second, activities to check rules and parent-teacher meetings; third, the supporting and inhibiting factors of the teacher's belief in implementing noble character development strategies for students. The supporting factors are the existence of school traditions, student awareness, teacher cooperation in fostering students' noble character, as well as parental support and motivation. While the inhibiting factors are the background of less supportive students and the social environment (association) that is less supportive.